Physical fitness of public elementary school boys and girls, ages 11 to 14, in the Division of Misamis Oriental - Llamera, Megdonio R. 1933- (s.n.], 1973)
The purpose of the study is to determine the physical fitness status of public school boys and girls, aged 11-14 in the division of Misamis Oriental, by comparing their performance in the ICSPFT Physical Performance Battery with the National Norms of this test, and to construct percentile norms in the different items of the ICSPFT Physical Performance Battery. The study provides norms in physical fitness for Misamis Oriental which will serve as a basis for the meaningful interpretation of individual or group performances within the Division. The physical fitness status of public school boys and girls in the Division can be appraised meaningfully by comparing their average scores with the National Norm.